TEKNIK LOLOS SERTIFIKASI DOSEN DI UNIVERSITAS SELAMAT SRI KENDAL - FZI; AGENG; adminjamet, adminjamet (Jurnal AbdiMas Ekonomi Terapan, 2023)
In order to improve competence, especially in the field of teaching, lecturers at Selamat Sri University need to conduct training, seminars, or other activities that support the development of knowledge. And we intend to help in the context of community service, namely providing training to provide knowledge on how to pass the lecturer certification technique. From the identification of existing problems, a problem that will be solved in community service can be formulated, namely how existing lecturers can improve their competence, one way that needs to be done is to be able to pass lecturer certification. The implementation of this community service has the aim of providing insight, knowledge, and practice to participants regarding the efforts that must be fulfilled in order to pass lecturer certification. So that all lecturers are aware of the importance of competence, including as lecturers whose competence can be recognized by the state with the issuance of educator certificates (PP 37/2009). The output target resulting from this community service is to increase the knowledge of lecturers as educators to be better prepared to take part in the lecturer certification process. This community service activity contributes to the institution. Because this is an effort to increase accreditation in study programs, if most of the existing lecturers already have educator certificates.